Syndromic and biological screening for sexually transmitted infections in female sex workers in Côte d’Ivoire: the ANRS 12381 PRINCESSE cohort study - Nouaman, Marcellin N’zebo; Coffie, Patrick Ahuatchi; Agoua, Aline A.; Zébago, Clémence; Dao, Hervé Z.; Kissi, Evelyne; Lenaud, Severin; Anatole, Mian; Becquet, Valentine; Plazy, Mélanie; Dabis, François; Eholie, Serge; et al. (Frontiers in Public Health, 2025)
BackgroundFemale sex workers (FSWs) are at high risk of contracting STIs, in particular in Sub-Saharan Africa. The implementation of oral HIV pre-exposure prophylaxis provided an opportunity to draw attention to the sexual health needs of FSWs. Innovative strategies to screen for and reduce the burden of STIs is thus a priority. This study describes STI screening among FSWs enrolled in the PRINCESSE project in Côte d’Ivoire.MethodsThe PRINCESSE project (2019–2023) was an interventional cohort of FSWs ≥18 years, evaluating a comprehensive, community-based sexual and reproductive health care package, including the management of STIs, offered through mobile clinics operating on prostitution sites in San Pedro area. HIV testing and syndromic STI testing were offered at baseline and every 3 months. Biological testing of Chlamydia trachomatis (CT) and Neisseria gonorrhoeae (NG) was offered annually. Clinical forms included sociodemographic, behavioral and sex-work-related characteristics. We describe baseline characteristics, coverage of clinical examination, and vaginal, anal swab collection. Social, behavioral and sex work-related factors associated with an STI syndromic diagnosis were explored. A multivariable logistic regression model was used to identify factors associated with diagnosing a symptomatic STI.Results489 FSWs were included in the PRINCESSE cohort. Median age was 29 years (24–35 years), 28.6% had had sex without a condom in the last 7 days. The prevalence of HIV at baseline was 10.5%. Only one case of HIV seroconversion was observed during the project. The most frequent symptom was ano-vaginal discharge (19.1%). The prevalence of STI based on clinical symptoms was 26.6%. The proportion of vaginal swab samples for which the PCR result was positive was 8.0% for CT and 4.0% for NG. Only age remained significantly associated with diagnosing a symptomatic STI in the multivariable analysis.ConclusionThis study revealed a high prevalence of HIV and STIs, similar to national estimates among FSWs enrolled in a sexual health cohort. Screening for these generically asymptomatic bacterial STIs must be combined with the syndromic approach used in key populations, especially with the introduction of new PrEP programs, to reduce the exposure of individuals in these populations to STIs.